Enhanced Cardiomyocyte Function in Hypertensive Rats With Diastolic Dysfunction and Human Heart Failure Patients After Acute Treatment With Soluble Guanylyl Cyclase (sGC) Activator - Kolijn, Detmar; Kovács, Árpád; Herwig, Melissa; Lódi, Mária; Sieme, Marcel; Alhaj, Abdulatif; Sandner, Peter; Papp, Zoltán; Reusch, Peter H.; Haldenwang, Peter; Falcão-Pires, Ines; Linke, Wolfgang A.; et al. (Frontiers in Physiology, 2020)
Aims Our aim was to investigate the effect of nitric oxide (NO)-independent activation of soluble guanylyl cyclase (sGC) on cardiomyocyte function in a hypertensive animal model with diastolic dysfunction and in biopsies from human heart failure with preserved ejection fraction (HFpEF). Methods Dahl salt-sensitive (DSS) rats and control rats were fed a high-salt diet for 10 weeks and then acutely treated in vivo with the sGC activator BAY 58-2667 (cinaciguat) for 30 min. Single skinned cardiomyocyte passive stiffness (Fpassive) was determined in rats and human myocardium biopsies before and after acute treatment. Titin phosphorylation, activation of the NO/sGC/cyclic guanosine monophosphate (cGMP)/protein kinase G (PKG) cascade, as well as hypertrophic pathways including NO/sGC/cGMP/PKG, PKA, calcium–calmodulin kinase II (CaMKII), extracellular signal-regulated kinase 2 (ERK2), and PKC were assessed. In addition, we explored the contribution of pro-inflammatory cytokines and oxidative stress levels to the modulation of cardiomyocyte function. Immunohistochemistry and electron microscopy were used to assess the translocation of sGC and connexin 43 proteins in the rat model before and after treatment. Results High cardiomyocyte Fpassive was found in rats and human myocardial biopsies compared to control groups, which was attributed to hypophosphorylation of total titin and to deranged site-specific phosphorylation of elastic titin regions. This was accompanied by lower levels of PKG and PKA activity, along with dysregulation of hypertrophic pathway markers such as CaMKII, PKC, and ERK2. Furthermore, DSS rats and human myocardium biopsies showed higher pro-inflammatory cytokines and oxidative stress compared to controls. DSS animals benefited from treatment with the sGC activator, as Fpassive, titin phosphorylation, PKG and the hypertrophic pathway kinases, pro-inflammatory cytokines, and oxidative stress markers all significantly improved to the level observed in controls. Immunohistochemistry and electron microscopy revealed a translocation of sGC protein toward the intercalated disc and t-tubuli following treatment in both control and DSS samples. This translocation was confirmed by staining for the gap junction protein connexin 43 at the intercalated disk. DSS rats showed a disrupted connexin 43 pattern, and sGC activator was able to partially reduce disruption and increase expression of connexin 43. In human HFpEF biopsies, the high Fpassive, reduced titin phosphorylation, dysregulation of the NO–sGC–cGMP–PKG pathway and PKA activity level, and activity of kinases involved in hypertrophic pathways CaMKII, PKC, and ERK2 were all significantly improved by sGC treatment and accompanied by a reduction in pro-inflammatory cytokines and oxidative stress markers. Conclusion Our data show that sGC activator improves cardiomyocyte function, reduces inflammation and oxidative stress, improves sGC–PKG signaling, and normalizes hypertrophic kinases, indicating that it is a potential treatment option for HFpEF patients and perhaps also for cases with increased hypertrophic signaling.